Gender identity and sport: is the playing field level? - Reeser, J. C. (British Journal of Sports Medicine, 2005)
This review examines gender identity issues in competitive sports, focusing on the evolution of policies relating to female gender verification and transsexual participation in sport. The issues are complex and continue to challenge sport governing bodies, including the International Olympic Committee, as they strive to provide a safe environment in which female athletes may compete fairly and equitably.